Plato's Cratylus : Argument, Form, and Structure - Riley, Michael W., (Brill Book Archive Part 1, ISBN: 9789004472495., 2005)
This book explains how the Cratylus , Plato's apparently meandering and comical dialogue on the correctness of names, makes serious philosophical progress by its notorious etymological digressions. While still a wild ride through a Heraclitean flood of etymologies which threatens to swamp language altogether, the Cratylus emerges as an astonishingly organized evaluation of the power of words.